Examining Healthcare Practitioners’ Perceptions of Virtual Physicians, mHealth Applications, and Barriers to Adoption: Insights for Improving Patient Care and Digital Health Integration - Alzghaibi H (International Journal of General Medicine)
Haitham Alzghaibi Department of Health Informatics, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi ArabiaCorrespondence: Haitham Alzghaibi, Email halzghaibi@qu.edu.saIntroduction: Mobile health (mHealth) applications have transformed healthcare by enhancing access to medical information, facilitating remote consultations, and improving patient engagement. Despite their potential, adoption challenges persist, particularly concerning usability, integration with existing healthcare systems, and user trust. The Sehhaty application, a national digital health platform in Saudi Arabia, exemplifies these challenges. Identifying the barriers that hinder healthcare practitioners’ engagement with mHealth applications is crucial for optimising their implementation and ensuring equitable access to healthcare services.Aim: This study examines healthcare practitioners’ perceptions of mHealth applications, with a specific focus on the Sehhaty app, to identify key adoption barriers. It further aims to provide recommendations for enhancing usability, accessibility, and integration within existing healthcare infrastructures.Methods: A cross-sectional study was conducted among 574 secondary healthcare practitioners (SHCPs), including physicians, nurses, and administrative staff, working in secondary healthcare centres across Saudi Arabia. Data were collected using a structured questionnaire assessing ten primary barriers to mHealth adoption, including technical, usability, training, integration, privacy, organisational, communication, financial, and productivity-related challenges. The reliability of the instrument was evaluated using Cronbach’s alpha, and descriptive statistics (frequencies, means, standard deviations) were computed. Correlation analysis was conducted to examine interrelationships among the identified barriers, providing insights into how different factors influence adoption. Data analysis was performed using SPSS (version 29) and R software.Results: The questionnaire demonstrated excellent internal consistency (Cronbach’s α = 0.95). The most significant barriers identified included Technical Barriers (Mean = 3.32), Usability Barriers (Mean = 3.05), and Integration and Workflow Challenges (Mean = 3.20). Participants reported frequent technical glitches, slow system performance, and poor compatibility with existing healthcare platforms. Usability concerns, such as complex navigation and excessive steps required to complete tasks, further hindered adoption. Integration challenges, including lack of interoperability with electronic health records, were also highlighted. Privacy and security concerns (Mean = 3.26) emerged as a significant factor affecting trust in the application. Correlation analysis revealed strong interdependencies among barriers, with Technical Barriers correlating with Usability Barriers (r = 0.69) and Integration and Workflow Barriers (r = 0.62), underscoring the compounded effect of these challenges on user adoption.Conclusion: Healthcare practitioners encounter multiple barriers in adopting the Sehhaty app, predominantly related to technical performance, usability, and system integration. Addressing these challenges requires targeted improvements in interface design, system interoperability, and technical support. Future research should incorporate patient perspectives, examine long-term adoption trends, and evaluate the impact of mHealth applications on clinical efficiency and patient outcomes. The study’s findings provide critical insights for policymakers, healthcare institutions, and technology developers seeking to enhance mHealth usability, digital health integration, and healthcare accessibility in Saudi Arabia’s evolving healthcare landscape.Keywords: mHealth adoption, Sehhaty application, healthcare practitioners, usability barriers, digital health integration, Saudi Arabia